Análise de desempenho de algoritmos de roteamento de nodos em uma rede de sensores sem fio aplicada a cidades inteligentes - Gomes, Rafael Ogayar (2018)
With the advancement of research involving Smart Cities, most of these are focused on the iteration between sensors and actuators, however, we can cite the problem with packet routing that has been studied, due to the need to obtain better communication between all the nodes and also without the loss of packets, aspects such as energy, reach and signal dispersion are crucial points in this subject. In this work, we performed studies and analysis of some routing algorithms (OADV, OSDV, DSR) which are the most used for applications, because they work in a satisfactory way with node mobility. The analysis of each algorithm was carried out in the different scenarios, and these will be shown during the development of this work, arriving at the conclusion of which more suitable to be used in different situation, location and specific specification, such as open field, cities, houses, buildings.